Behavior of the brown-rot fungus Gloeophyllum trabeum on thermally-modified Eucalyptus grandis wood - Calonego, Fred Willians [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP]; Negrão, Djanira Rodrigues [UNESP]; Rocha, Cinthia Dias [UNESP]; Minhoni, Marli Teixeira De Almeida [UNESP]; Latorraca, João Vicente; Severo, Elias Taylor Durgante [UNESP] (Universidade Federal Rural do Rio de Janeiro, Instituto de Florestas, 2013)
In this study, we aimed evaluate the behavior of the brown-rot fungus Gloeophylum trabeum and white-rot fungus Pycnoporus sanguineus on thermally-modified Eucalyptus grandis wood. To this end, boards from five-year-eleven-month-old E. grandis trees, taken from the Duratex-SA company stock, were thermally-modified between 180 ºC and 220 ºC in the Laboratory of Wood Drying and Preservation at Universidade Estadual Paulista - UNESP, Botucatu, Sao Paulo state Brazil. Samples of each treatment were tested according to the ASTM D-2017 (2008) technical norm. The accelerated decay caused by the brown-rot fungus G. trabeum was compared with the decay caused by the white-rot fungus P. sanguineus, studied by Calonego et al. (2010). The results showed that (1) brown-rot fungus caused greater decay than white-rot fungus; and (2) the increase in temperature from 180 to 220 ºC caused reductions between 28.2% and 70.0% in the weight loss of E. grandis samples incubated with G. trabeum.

O objetivo deste estudo foi avaliar o comportamento do fungo de podridão parda Gloeophylum trabeum e do fungo de podridão branca Pycnoporus sanguineus sobre a madeira de Eucalyptus grandis modificada termicamente. Tábuas de árvores de E. grandis com cinco anos e 11 meses de idade, da empresa Duratex-SA, foram modificadas termicamente entre 180 ºC e 220 ºC no Laboratório de Secagem e Preservação de Madeiras da UNESP, Botucatu-SP, Brasil. Corpos de prova de cada tratamento foram testados, de acordo com a norma técnica ASTM D-2017 (2008). O apodrecimento acelerado causado pelo fungo de podridão parda G. trabeum foi comparado com o do fungo de podridão branca P. sanguineus, estudado por Calonego et al. (2010). Os resultados mostraram que (1) o apodrecimento causado pelo fungo de podridão parda foi maior que o de podridão branca e (2) o aumento da temperature de 180 para 220 ºC ocasionou reduções de 28,2% a 70,0% na perda de massa dos corpos de prova de E. grandis incubados com o G. trabeum.
Comportamento do fungo de podridão parda Gloeophyllum trabeum na madeira de Eucalyptus grandis modificada termicamente
Keywords: resistência ao apodrecimento; G. trabeum; madeira tratada termicamente; eucalipto; fungos apodrecedores; decay resistance; G. trabeum; heat-treated wood; eucalypts; rot fungi